Outcome of T- Large Granular Lymphocyte Leukemia from a Tertiary Care Centre in North India - Athar, Rizwan; Singh, Ipra; Kashyap, Rajesh; Rahman, Khaliqur; Gupta, Ruchi; Chandra, Dinesh (Asian Pacific Journal of Cancer Biology, 2025)
Introduction: T-cell large granular lymphocytic leukemia (T-LGL) is a rare disorder with a frequency of less than 5% of the lymphoproliferative disorders (LPD) . T-LGL is characterized by persistent increase in LGLs (2 to 20×109 /L) on peripheral blood in absence of a reactive cause. Material and methods: In this retrospective study for a period of 66 months (January 2019 to June 2024), all the samples received in the flow cytometry lab with a suspicion of LPD were screened. A stain-lyse-wash protocol was used and samples were stained with Two to three tubes of 8-10 color combinations. The clinical and laboratory features of the patients diagnosed as T-LGL were retrieved from computerized Hospital Information System and were further analyzed. Results: A total of 341 samples were analysed during this period which were diagnosed as B cell neoplasm 87%, T cell neoplasm 8%, NK-cell neoplasm 1% and reactive lymphoid proliferation 4%. The T LGL comprised of 10 (2.9%) cases. Mean age of presentation was 57.3 years, with a male:female ratio of 1.25:1. Approximately 60% patients had BM involvement, 50% had autoimmune disorder and 40% had splenomegaly. Patients were treated with corticosteroids, weekly methotrexate and cyclosporine, if required. 7/10(70%) patients are on follow up, are stable and in remission. Two patients died while one was lost to follow up. Conclusion: The frequency of T LGL noted in our study was 2.9% of the lymphoproliferative disorders. T LGLs had an indolent course and responds well to treatment.